Broadening of cohesinopathies: exome sequencing identifies mutations in ANKRD11 in two patients with Cornelia de Lange‐overlapping phenotype. Issue 1 (25th February 2015) - Parenti, I.; Gervasini, C.; Pozojevic, J.; Graul‐Neumann, L.; Azzollini, J.; Braunholz, D.; Watrin, E.; Wendt, K.S.; Cereda, A.; Cittaro, D.; Gillessen‐Kaesbach, G.; Lazarevic, D.; et al.
Abstract : Cornelia de Lange syndrome (CdLS) and KBG syndrome are two distinct developmental pathologies sharing common features such as intellectual disability, psychomotor delay, and some craniofacial and limb abnormalities. Mutations in one of the five genes NIPBL, SMC1A, SMC3, HDAC8 or RAD21, were identified in at least 70% of the patients with CdLS. Consequently, additional causative genes, either unknown or responsible of partially merging entities, possibly account for the remaining 30% of the patients. In contrast, KBG has only been associated with mutations in ANKRD11 . By exome sequencing we could identify heterozygous loss‐of‐function mutations in ANKRD11 in two patients with the clinical diagnosis of CdLS. Both patients show features reminiscent of CdLS such as characteristic facies as well as a small head circumference which is not described for KBG syndrome. Patient A, who carries the mutation in a mosaic state, is a 4‐year‐old girl with features reminiscent of CdLS. Patient B, a 15‐year‐old boy, shows a complex phenotype which resembled CdLS during infancy, but has developed to a more KBG overlapping phenotype during childhood. These findings point out the importance of screening ANKRD11 in young CdLS patients who were found to be negative for mutations in the five known CdLS genes.